When Tears and Prayers are not Enough - Mário Farelo (Studia Historica. Historia Medieval, 2022)
This text focuses on the ecclesiastical tax transfers in favour of the Portuguese Crown in the late medieval period, through an analysis of the typology of taxes, the chronology of its granting and the justifications presented for its perception. While the justifications given by the monarchy remain framed by the legitimacy conferred by canon law, the clerics’ resistance to its payment reveal an argument based on reality and on the good will to satisfy the fiscal needs of the Portuguese monarchs.